Criminal Policy against Economic Offenses in Kazakhstan - AMANZHOLOVA, Botagoz A.; BAZAROVA, Gulmira S.; KALGUZHINOVA, Aigul M.; UALIEVA, Zhanna B. (Journal of Advanced Research in Law and Economics, 2016)
The paper reviews the specifics in economic crime regulation in Kazakhstan. To define a current state of the fight against economic crimes, the authors compare the Criminal Code of the Republic of Kazakhstan of 1997 and that of 2014. The analysis of changes made to the national criminal legislation includes theoretical justification of new laws. Common patterns of changes in general and economic crimes in particular have been reviewed. There are criminalization of socially dangerous acts, decriminalization of crimes, and specification of qualifying crime attributes; penalization; depenalisation; changed place of crime components in the Special Part of the Criminal Code; the new chapter separation. The research of intensity in making changes in statutory regulations on economic crimes with tendencies towards ensured economic security from criminal encroachments has shown that the spent law making efforts do not always lead to expected results of an effective decrease in crime. Toughening of criminal penalty, the expanded number of the qualifying and especially qualifying signs in certain cases and in an insignificant degree appear to be tools in demand to counteract economic crimes.
Keywords: criminal policy; legal policy; economic crime; Criminal Code; Republic of Kazakhstan